Thoughts about Information Management Systems at the University of Costa Rica: Advantages and disadvantages of its Administrative System - Araya Garita, Walter (2015)
This is a descriptive analysis on management information systems at institutions of higher learning. Basic educational management theories are reviewed including, information systems, knowledge and databases required for understanding the need, functionality and success of a management system. This paper also focuses on the current administrative system at the University of Costa Rica and describes applications developed at the institution as an effort to address the lack of such systems. In addition, the advantages and disadvantages of university administrative systems were classified based on the information that was analyzed. It is concluded that information management systems are indispensable at institutions for higher learning. The University of Costa Rica cannot ignore this situation and must strategically leverage on the systems it uses in order to convert the data to information in the different academic sectors.